EVOLUTION OF VACCINE PREVENTION - IMPROVEMENT TO DEFENCES AGAINST PNEUMOCOCCUS - M.V. Fedoseenko (Union of pediatricians of Russia, 2010)
In March 2010, the International Symposium on Pneumococci and Pneumococcal Diseases was held in Tel-Aviv. Experts from 70 countries across the world gathered to discuss the latest scientific advances related to epidemiology and diagnostics, treatment and prevention of the pneumococcal infection. The latest achievements in microbiology and genetics helped discover the «genetic» portrait of S. pneumoniae and assess its phenotypic properties. Pneumococcal infection, which is a leading cause of death throughout the world, is vaccine-controlled. Multiple scientific studies conducted in different parts of the world reliably confirmed the safety, immunogenicity and efficacy of currently available pneumococcal vaccines and related vaccination schedules. An ongoing exchange of knowledge about pneumococcus is required to optimize the clinical and economic efficacy of pneumococcal vaccination. Developing new vaccines capable of expanding the coverage of pneumococcus immunotypes, as well as support more sustainable immune defense in high-risk patients (children, elderly people and patients with chronic pathologies).Key words: vaccinal prevention, pneumococcal infection, advances, safety, efficacy, children. (Pediatric Pharmacology. - 2010; 7(6):22-25)